The differences between tattooed and non-tattooed individuals In body image coping strategies and attitudes toward cosmetic surgery - Kuş, Yasemin; Tan, Ezgi (The European Research Journal, 2023)
Objectives: This study aims to compare tattooed and non-tattooed individuals in terms of their attitude toward cosmetic surgery in multiple motivational sources. Also, the differences across groups are examined by use of three different body image coping strategies Methods: Participants were 108 tattooed and 202 non tattooed individuals. Respondents were 267 females and 43 males from Turkey in a private university. Their age ranged between 18 to 29, and the mean age is 21. Results: The analysis indicated that tattooed individuals had a more positive attitude toward any cosmetic surgery application. Also, there is a difference in appearance fixation coping strategy between two groups. Tattooed individuals prefered to use appearance fixation to cope with their body image. However, the effect size of this difference was negligible to small. Conclusions: These results suggest that tattooed and non- tattooed individuals differ remarkably in cosmetic surgery attitude. Having tattoos has an effect on cosmetic surgery motivational sources. Tattooed individuals are more motivated and look positive toward cosmetic surgery interventions than non-tattooed individuals. Also, tattooed individuals use more appearance fixation coping strategy.